2014
DOI: 10.1002/btpr.1857
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of expression and activity levels of primary rat hepatocyte detoxication genes under various flow rates and cell densities in microfluidic biochips

Abstract: We investigated the behavior of primary rat hepatocytes in biochips using a microfluidic platform (the integrated dynamic cell culture microchip). We studied the effects of cell inoculation densities (0.2-0.5 × 10(6) cells/biochip) and perfusion flow rates (10, 25, and 40 µL/min) during 72 h of perfusion. No effects were observed on hepatocyte morphology, but the levels of mRNA and CYP1A2 activity were found to be dependent on the initial cell densities and flow rates. The dataset made it possible to extract a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
(66 reference statements)
0
26
0
Order By: Relevance
“…The feasibility of carrying out transcriptomic, proteomic, metabolic and toxicologic characterization with this arrangement, was illustrated and showed that HepG2/C3a phenotypic responses including albumin secretion, sensitivity to acetaminophen toxicity, and relative expression of CYP450 and transport genes appeared more physiologically close to primary hepatocytes in the microfluidic compared to static petri dish culture, a result that may in part due to the quasi-3D aggregate structures that form in regions of the recessed structures [74,79,80][8184]. Initial studies analyzing primary rat [85,86] and human [74,87] cells in short term culture (4 days) indicate that these cells were less likely to form aggregates, and optimization of operating conditions for these cells is evolving. The results assessing drug metabolism with cryopreserved human cells are instructive in two key ways, first showing that these cells attach and survive in both the recessed features as well as the top of the PDMS exposed directly to flow.…”
Section: Bioreactorsmentioning
confidence: 99%
“…The feasibility of carrying out transcriptomic, proteomic, metabolic and toxicologic characterization with this arrangement, was illustrated and showed that HepG2/C3a phenotypic responses including albumin secretion, sensitivity to acetaminophen toxicity, and relative expression of CYP450 and transport genes appeared more physiologically close to primary hepatocytes in the microfluidic compared to static petri dish culture, a result that may in part due to the quasi-3D aggregate structures that form in regions of the recessed structures [74,79,80][8184]. Initial studies analyzing primary rat [85,86] and human [74,87] cells in short term culture (4 days) indicate that these cells were less likely to form aggregates, and optimization of operating conditions for these cells is evolving. The results assessing drug metabolism with cryopreserved human cells are instructive in two key ways, first showing that these cells attach and survive in both the recessed features as well as the top of the PDMS exposed directly to flow.…”
Section: Bioreactorsmentioning
confidence: 99%
“…In addition, many studies have reported that mRNA expression of genes involved in xenobiotic metabolism and transport, including CYP1A1, 1 A2, 2B6, 2C9, 3 A4, multidrug resistance protein 1, MRP2, and UDP-glucuronosyltransferase, was upregulated by medium flow (Baudoin et al 2014;Dash et al 2013;Vinci et al 2011). In our study, hepatocytes exposed to flow conditions expressed higher levels of hepatocyte-specific markers, such as CYP1A2, MRP1, and UGT1A5, over 13 days.…”
Section: Discussionmentioning
confidence: 56%
“…As additional in vitro system, one could consider to use rat primary hepatocytes. These cells have been demonstrated to retain high mRNA levels of CAR and other xenobiotic receptors, as well as Phase I and Phase II genes (Baudoin et al 2014). This may improve the detection of CAR activators, which were missed using PMH and mESC.…”
Section: Discussionmentioning
confidence: 98%